Philosophy of education - Noddings, Nel, 1929- (Westview Press, a member of The Perseus Books Group, 2016)
"The first edition of Nel Noddings' Philosophy of Education was acclaimed as the "best overview in the field" by the journal Teaching Philosophy and predicted to "become the standard textbook in philosophy of education" by Educational Theory. This classic text, originally designed to give the education student a comprehensive look at philosophical thought in relation to teaching, learning, research, and educational policy, has now been updated to reflect the most current thinking in the field. A revised chapter on Logic and Critical Thinking makes the topic more accessible to students and examines how critical thinking plays a role in light of the new Common Core standards. Philosophy of Education introduces students to the evolution of educational thought, from the founding fathers to contemporary theorists, with consideration of both analytic and continental traditions. This is an essential text not only for teachers and future teachers, but also for anyone needing a survey of contemporary trends in philosophy of education"--Resumé vydavatele
Keywords: filozofie výchovy; dějiny filozofie; philosophy of education; history of philosophy; učební texty; educational texts